How Do Service Quality, Experiences and Enduring Involvement Influence Tourists' Behavior? An Empirical Study in the Picasso and Miró Museums in Barcelona. (25th January 2017) - Forgas‐Coll, Santiago; Palau‐Saumell, Ramon; Matute, Jorge; Tárrega, Salomé
Abstract: This study develops an integrated model that examines how service quality, perceived experiences and enduring involvement determine tourists' behavior. The model proposes that enduring involvement has both a direct and moderating influence on tourists' satisfaction with the destination. Data were collected from 1091 visitors of two museums in Barcelona: the Picasso Museum and the Miró Foundation. The results suggest that visit experience, service quality and involvement are drivers of satisfaction. Satisfaction influences the behavioral intentions of visitors to the museum. In addition, the visitors' level of art involvement negatively moderates the influence of perceived quality and experience on tourists' satisfaction. Copyright © 2017 John Wiley & Sons, Ltd.